دراسة مورفولوجية وتصنيفية لفصيلة خنافس البذور Bruchidae( Coleoptera: Insecta) في سوريا (Latakia University Journal -Biological Sciences Series, 2019)
تم جمع 422 عينة من مناطق مختلفة في سوريا خلال أعوام2011-2010-2009 من بذور وثمار العوائل النباتية لحشرات فصيلة خنافس البذور Bruchidae، أخذ منها 133 أنثى و141 ذكر. درست من الناحيتين المورفولوجية والتصنيفية من خلال وضع مفاتيح تصنيفية لتحت - الفصائل والأجناس والأنواع المنتشرة في سوريا بالاعتماد على الصفات المورفولوجية المهمة لها، أدت الدراسة إلى تعريف عشرة أنواع تتبع لخمسة أجناس وتحت - فصيلتين، هي: Bruchuserviو B. lentisو B. pisorumوB. rufimanusوCallosobruchuschinensisوC. maculatusوC. analisوAcanthoscelidesobtectusوStator limbatusوSpermophagussericeus . تم تسجيل أربعة أنواع للمرة الأولى في سوريا هي: B. lentisوC. analisوS. limbatusوS. sericeus. In this study 422 samples were collected from different locations in Syria during 2009 – 2010 – 2011 from seeds and fruits of Bruchids host plants. Morphological and taxonomical aspects of 133 females and 141 males have been studied. Identification Keys of sub families, genera and species were recorded according to the most important taxonomic features. A total of ten species belonging to five genera and two sub - families are recorded and classified, and these are: Bruchuservi, B. lentis, B. pisorum, B. rufimanus, Callosobruchuschinensis, C. maculatus, C. analis, Acanthoscelidesobtectus, Stator limbatus, Spermophagussericeus .The following species B. lentis, C. analis, S. limbatus, S. sericeus. could be considered the first ever recorded in Syria.